(untitled) (Asian Journal of Medical and Biological Research, 2026)
The Nursing Process (NP) is a structured, patient-centered framework essential for delivering systematic and high-quality nursing care. Despite its global acceptance, its implementation remains inconsistent in low-resource settings such as Bangladesh, where a persistent gap exists between theoretical knowledge and clinical practice. This study aimed to assess nurses’ knowledge of the nursing process and identify factors influencing its implementation in a tertiary care hospital in Dhaka. A cross-sectional study was conducted among 195 nurses between April and June 2024 using a structured, interviewer-administered questionnaire covering socio-demographic characteristics, knowledge of the nursing process, and perceived barriers to its implementation. Data were analyzed using descriptive statistics and chi-square tests, with statistical significance set at P < 0.05. The mean age of participants was 29.62 ± 5.28 years, and most were female (85.60%). More than half held a BSc in Nursing (53.30%), and 83.63% had 1–10 years of experience, while 16.37% had 11–20 years of experience. Although 51.79% reported excellent knowledge of the nursing process and 68.21% gained knowledge during college lectures, only 22.56% received adequate training after qualification, and none (100%) reported implementing the NP in clinical practice. Knowledge was significantly associated with age (χ²=7.66, P=0.006), education (χ²=6.27, P=0.012), and experience (χ²=8.61, P=0.003), but not with gender or religion. Major barriers included lack of specific training for applying the nursing process (81.54%) and absence of a standardized nursing process documentation format (77.95%), followed by inadequate administrative follow-up (72.31%), lack of institutional education (68.72%), and cultural belief influence (69.74%). Additional barriers included inadequate skills (60.51%), insufficient information (54.87%), and insufficient motivation (47.69%). No significant association was found between demographic variables and perceived barriers, although a borderline association was observed with age (χ²=3.43, P=0.064). The study concludes that despite moderate theoretical knowledge, the nursing process is not implemented in practice due to systemic and organizational barriers. These findings highlight the need for urgent policy-level interventions, including structured nursing process training, standardized documentation systems, and stronger institutional supervision to improve translation of knowledge into practice. Strengthening training and institutional support is essential to bridge the gap and enhance nursing care quality. Asian J. Med. Biol. Res. 2026, 12(2), 24-33